2023
DOI: 10.1038/s41467-023-38057-9
|View full text |Cite
|
Sign up to set email alerts
|

Sediment delivery to sustain the Ganges-Brahmaputra delta under climate change and anthropogenic impacts

Abstract: The principal nature-based solution for offsetting relative sea-level rise in the Ganges-Brahmaputra delta is the unabated delivery, dispersal, and deposition of the rivers’ ~1 billion-tonne annual sediment load. Recent hydrological transport modeling suggests that strengthening monsoon precipitation in the 21st century could increase this sediment delivery 34-60%; yet other studies demonstrate that sediment could decline 15-80% if planned dams and river diversions are fully implemented. We validate these mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 119 publications
0
15
0
Order By: Relevance
“…As a matter of fact, the amount of land loss and gain are achieved as resultant of the natural processes and the implemented protective measures as well. On the other hand, the land gain in the major estuarine systems is exhibiting positive outcomes, while the amount of gaining new land exceeds the land loss that implicitly indicates that GBM delta still has potential to counterbalance the relative sea level rise which has been confirmed by several recent studies (Rahman, and Haque et al, 2022;Raff and Goodbred et al, 2023). Like the major rivers, the net outcome of the land loss and gain in the estuarine systems are also resulting from natural processes and anthropogenic interventions such as cross-dams and TRM (Rahman et al, 2022), and often, the forced land reclamation in one area has several consequences somewhere else (WARPO, BUET, 2021) if it not supported naturally.…”
Section: Introduction 11 Flow-sediment Regime and Morpho-dynamic Resp...mentioning
confidence: 74%
“…As a matter of fact, the amount of land loss and gain are achieved as resultant of the natural processes and the implemented protective measures as well. On the other hand, the land gain in the major estuarine systems is exhibiting positive outcomes, while the amount of gaining new land exceeds the land loss that implicitly indicates that GBM delta still has potential to counterbalance the relative sea level rise which has been confirmed by several recent studies (Rahman, and Haque et al, 2022;Raff and Goodbred et al, 2023). Like the major rivers, the net outcome of the land loss and gain in the estuarine systems are also resulting from natural processes and anthropogenic interventions such as cross-dams and TRM (Rahman et al, 2022), and often, the forced land reclamation in one area has several consequences somewhere else (WARPO, BUET, 2021) if it not supported naturally.…”
Section: Introduction 11 Flow-sediment Regime and Morpho-dynamic Resp...mentioning
confidence: 74%
“…Intense seasonal or event-scale precipitation can increase river sediment discharge [98], thereby elevating nearshore TSM. Some studies at the geological scale, based on sedimentary records [99][100][101], also suggested that stronger monsoons result in increased sediment supply from rivers to the northern Bay of Bengal. However, it is difficult to distinguish TSM interannual variation caused by monsoonal variation as the relationship among monsoon, precipitation, and river discharge are linked.…”
Section: Land-use Change and Its Effects On Tsm In Estuariesmentioning
confidence: 99%
“…Given the expected future demand for sediments in order to keep pace with SLR, these long-term large-scale impacts should be accounted for when planning sediment extraction. Such planning would also need to account for a delayed response resulting from on the system's previous buffer capacity [21,79,80].…”
Section: Implications For Future Sediment Managementmentioning
confidence: 99%